ANCAMAN ALLAH SWT BAGI YANG KIKIR/ BAKHIL - Nur Asiah; Salamat Riadi (Pusat Riset dan Inovasi Nasional, 2023)
This miserly disease often afflicts people who strive in the way of Allah, and is the cause of the suffering of Muslims today and this trait is a disease that must be cured. This is a bad and despicable trait in all religious views, so that there are many verses in the Koran that explain miserliness and knowledge of the hadith content of Muslim history from Jabir, while the research method that will be used is library research, data collection techniques. for research is library study, namely by examining materials from theories related to the problems discussed based on books that are related and can support or support research.